2022
DOI: 10.5194/nhess-22-1559-2022
|View full text |Cite
|
Sign up to set email alerts
|

Assessing flooding impact to riverine bridges: an integrated analysis

Abstract: Abstract. Flood events are the most frequent cause of damage to infrastructure compared to any other natural hazard, and global changes (climate, socioeconomic, technological) are likely to increase this damage. Transportation infrastructure systems are responsible for moving people, goods and services, and ensuring connection within and among urban areas. A failed link in these systems can impact the community by threatening evacuation capability, recovery operations and the overall economy. Bridges are criti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In addition, scour was calculated for a return period of T=500 years [37]. It should be noted that, for the hydraulic study, masonry arch bridges are particularly vulnerable to scour due to the combination of their high stiffness and shallow bases [7].…”
Section: Hydrological and Hydraulic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, scour was calculated for a return period of T=500 years [37]. It should be noted that, for the hydraulic study, masonry arch bridges are particularly vulnerable to scour due to the combination of their high stiffness and shallow bases [7].…”
Section: Hydrological and Hydraulic Studiesmentioning
confidence: 99%
“…While seismic risks are crucial to consider, this research emphasizes hydrological risks, as bridges in Peru have demonstrated susceptibility to such phenomena as floods. It is noteworthy that flood-related incidents are a major contributor to bridge failures in river channels, causing flooding and scour in abutments and piers [7]. For instance, the El Niño Phenomenon between 2016 and 2017 resulted in the destruction of 449 bridges nationwide [8], underscoring the lack of resilience in Peru to extreme events [9].…”
Section: Introductionmentioning
confidence: 99%
“…Historic pre-instrumental records and longest stream flow 2 of 17 time series data have great significance in the design of hydraulic structures, namely, dams, bridges, and culverts [18]. Extreme rainfall, resulting in floods and scour, is the most dynamic cause of bridge failures [19,20]. Globally, numerous studies have been conducted on the effects of floods on infrastructure in different countries.…”
Section: Introductionmentioning
confidence: 99%
“…The most critical hazards to which they are exposed are hydrological [1][2][3][4], wherein the most recurrent failures are caused by floods that cause foundational movement [5]. Climate change directly influences hydrological events [4,6,7]. As the frequency of the maximum flood events increases, there are higher failure probabilities and an accelerated deterioration of bridges, which results in significant economic losses [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…As the frequency of the maximum flood events increases, there are higher failure probabilities and an accelerated deterioration of bridges, which results in significant economic losses [4,8]. Under such a premise, it becomes a matter of priority to meet regulatory and functionality requirements [6,9], especially considering that many bridges have completed their intended life cycle. Consequently, vulnerability studies become important support tools to make decisions based on scientific evidence and thus prioritize investments in important infrastructures such as bridges [10].…”
Section: Introductionmentioning
confidence: 99%